Bmi1 Severs as a Potential Tumor-Initiating Cell Marker and Therapeutic Target in Esophageal Squamous Cell Carcinoma. (20th August 2020) - Wang, Xiaochen; Li, Kang; Cheng, Maosheng; Wang, Ganping; Han, Hui; Chen, Fangfang; Liao, Wenjing; Chen, Zhi; Chen, Jianwen; Bao, Yong; Peng, Liang; Chen, Demeng
Abstract : Esophageal squamous cell carcinoma (ESCC) is a frequent malignant tumor with low 5-year overall survival. Targeting ESCC tumor-initiating cells (TICs) may provide a new research avenue to achieve better therapeutic effects of ESCC. However, the identity and characteristics of ESCC TICs remain poorly understood. Through genetic lineage tracing approach, we found that a group of Moloney murine leukemia virus insertion site 1- (Bmi1-) expressing cell populations present in the invasive front of the esophageal epithelium, providing a continuous flow of tumor cells for ESCC. Subsequently, we found that ablation of Bmi1 + cells from mice with ESCC led to inhibition of tumor growth. In addition, our results demonstrated that PTC-209, an inhibitor of Bmi1, was able to inhibit ESCC progression when combined with cisplatin. In summary, our data suggest that Bmi1 + cells serve as TICs in ESCC.